Epigenetic Dysregulation of Dopaminergic System by Maternal Cafeteria Diet During Early Postnatal Development. (1st January 2020) - Rossetti, M.F.; Schumacher, R.; Gastiazoro, M.P.; Lazzarino, G.P.; Andreoli, M.F.; Stoker, C.; Varayoud, J.; Ramos, J.G.
Highlights: Maternal cafeteria diet decreased the transcription of TH, DRD2 and DAT in the ventral tegmental area of neonatal offspring. In nucleus accumbens, maternal cafeteria diet reduced DRD1, DRD2 and DAT expression at postnatal day 10. The methylation status of dopaminergic gene promoters was affected by maternal diet. Abstract: Dopamine is a neurotransmitter crucial for motor, motivational, and reward-related functions. Our aim was to determine the effect of a palatable maternal diet on the transcriptional regulation of dopaminergic-related genes during perinatal development of rat offspring. For that, female offspring from dams fed with a control (CON) or a cafeteria (CAF) diet were sacrificed on embryonic day 21 (E21) and postnatal day 10 (PND10). Using micropunch techniques, ventral tegmental area (VTA) and nucleus accumbens (NAc) were isolated from brain's offspring. Bioinformatic analysis of the promoter regions, mRNA quantification and methylation studies were done. The increase in tyroxine hidroxylase (TH), dopamine receptor (DRD) 1 and ghrelin receptor (GHSR) expression in VTA and NAc from E21 to PND10 was correlated with changes in DNA methylation of their promoter regions. Maternal diet did not affect the expression patterns in E21. At PND10, maternal CAF diet decreased the transcription of TH, GHSR, DRD2 and dopamine transporter (DAT) in VTA. Interestingly, the changes in TH, DRD2 and DAT expression were related to the methylation status of their promoters. In NAc, maternal CAF diet reduced DRD1, DRD2 and DAT expression in the offspring at PND10, although alternations in the methylation patterns were only detected in DAT promoter. These results show the importance of maternal nutrition and provide novel insights into the mechanisms through which maternal junk-food feeding can affect reward system during development and early postnatal life. Particularly important is the expression decline of DRD2 given its physiological implication in obesity and addiction.